2011
DOI: 10.1002/anie.201105119
|View full text |Cite
|
Sign up to set email alerts
|

Protein α‐Turns Recreated in Structurally Stable Small Molecules

Abstract: α‐Turn mimics: α‐Turns in proteins vary in three sets of (ϕ, ψ) angles that determine peptide backbone shape and helical pitch. Structures of cyclic tetrapeptides 1 and 2 are shown to closely match two α‐turn types that are structurally influential at key sites in 20 proteins described. NMR and CD spectroscopy as well as MD simulations have been used to characterize these first examples of non‐helical α‐turns created in small molecules.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
24
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 20 publications
(25 citation statements)
references
References 30 publications
1
24
0
Order By: Relevance
“…Noteworthy is also the observation of strong NOEs between the amide proton of Ala 1 and the H γ1,2 of Glu 4, as expected from the intended cyclization (Figure c). However, as mentioned above, 3 J αHN coupling measurements are more in agreement with an alpha turn as previously reported (Hoang et al, , ) (Figure d), with a characteristic large value (~10 Hz) for the residue in position 2 of the N‐lock. Not surprisingly, no NOEs were observed with the corresponding linear tetrapeptide (not shown).…”
Section: Resultssupporting
confidence: 91%
See 1 more Smart Citation
“…Noteworthy is also the observation of strong NOEs between the amide proton of Ala 1 and the H γ1,2 of Glu 4, as expected from the intended cyclization (Figure c). However, as mentioned above, 3 J αHN coupling measurements are more in agreement with an alpha turn as previously reported (Hoang et al, , ) (Figure d), with a characteristic large value (~10 Hz) for the residue in position 2 of the N‐lock. Not surprisingly, no NOEs were observed with the corresponding linear tetrapeptide (not shown).…”
Section: Resultssupporting
confidence: 91%
“…Rather, the helix can be stabilized by hydrogen bonding between such amides and the side‐chain hydrogen bond acceptor atoms of capping residues (Asn, Ser, Thr, Asp, or Glu) at positions 1 and 4 (Figure a), and such arrangement, termed capping box, is often found in native protein structures (Harper & Rose, ; Jimenez, Munoz, Rico, & Serrano, ; Presta & Rose, ). Based on this simple observation, it was reported that a straightforward way to stabilize a linear peptide into a helix could be via a direct lactam bond between the N‐terminus amine and the side chain of a glutamic acid placed in position 4 (Figure b) (Hoang et al, , ). While simple molecular mechanics would predict that such arrangement is compatible to an ideal alpha‐helical peptide geometry (Figure b), more detailed studies using molecular dynamics and experimental CD amd NMR data in solution suggested that the peptide is slightly distorted and assumes an alpha turn conformation (Hoang et al, , ).…”
Section: Resultsmentioning
confidence: 99%
“…Structures were calculated in XPLOR-NIH [9b] using a dynamic simulated annealing protocol in a geometric force field and energy-minimized using the CHARMm force field. Pro6 and Ile1(Thz) form an a-turn [10] at the other end of 3. 0.2 ) or dihedral angle (!…”
Section: Angewandte Zuschriftenmentioning
confidence: 99%
“…Ghadiri and co-workers, for instance, 20,21 have used copper-mediated azide-alkyne cycloadditions to give the 13-membered rings E which were conformationally rigid. 22 In other illustrative work, Fairlie et al substituted β-amino acids into cyclic tetrapeptides and found some 13-membered ring systems, including F 23 and G 24 , that could be prepared efficiently, and were conformationally rigid. However, that same work showed similar, but conformationally heterogeneous , 13-membered ring systems.…”
Section: Introductionmentioning
confidence: 99%